Innovation system strengths and weaknesses in progressing sustainable technology: the case of Swedish biorefinery development. (10th September 2016) - Hellsmark, Hans; Mossberg, Johanna; Söderholm, Patrik; Frishammar, Johan
Abstract: Based on the combination of economic challenges and uncertain policy conditions in the United States, European Union, and elsewhere, the development of advanced biorefineries has progressed slower than anticipated. This has delayed the transition to a more sustainable and less carbon-intensive economy. In this article, we adopt the technological innovation system (TIS) approach to analyze advanced biorefinery development in Sweden, a front-runner country in current development. The analysis highlights a number of system strengths (e.g., long-term research funding; significant research infrastructure; strong actor networks) that have contributed to developing the Swedish TIS, but also important system weaknesses (e.g., weak coordination among ministries; lack of industrial absorptive capacity; unclear roles) inhibiting it. The article highlights a combination of four policy measures that build on the system strengths to address the system weaknesses: (a) the implementation of a deployment policy for creating domestic niche markets; (b) improved policy timing and more structured coordination among different governmental agencies; (c) the provision of stronger incentives for mature industries to invest in R&D and improve their absorptive capacity; and (d) improved organization and financing of existing research infrastructure. In addition to the empirical contribution, the article contributes with novel insights into the TIS framework by highlighting the dynamics between system strengths and weaknesses, and suggests that system strengths should be better emphasized in future TIS studies. Highlights: A technological innovation system (TIS) analysis of biorefineries in Sweden. Addresses the dynamics between system weaknesses and system strengths. System strengths provides opportunities for leveraging Swedish biorefinery development. Deployment policies are needed to shift TIS into the niche market phase. Policy timing and coordination are keys to avoid stagnation of the TIS.